PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA BERSUARA DENGAN INTEGRASI QR CODE MATERI BUMIKU SAYANG BUMIKU MALANG PADA SISWA KELAS V SD NEGERI 2 KETEPUNG.: PENELITIAN PENGEMBANGAN - Listari, Hardiana Rizqiyani; Wulan Trisnawaty; Sugiyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT Based on the observations and interviews results, students at SD Negeri 2 Ketepung feel bored quickly when participating in learning activities. This problem is because teachers' learning methods and media tend to be traditional and monotonous. Conventional learning methods and media are currently insufficient to attract the attention of children accustomed to digital devices. The technique used in this study is research and development (R&D) with the ADDIE model, with the stages of analysis, design, development, implementation, and evaluation. Data collection techniques in the study were carried out through questionnaires. The sound Snakes and Ladders game media with QR Code integration was validated by five material experts and five media experts. It was implemented on 12 fifth-grade students of SD Negeri 2 Ketepung to determine their responses. Based on the research results, the snake and ladder learning media with QR Code integration for the material My Earth Loves My Earth Malang was developed in accordance with the ADDIE stage. The quality of the learning material on the media obtained a percentage of 98% with the